Vaiphei Pau Matdân Leh Thuphuak | Vaiphei Grammar and Composition, Part - I, Class-XI and XII - (:unkn) unknown (Vaiphei Literature Society Manipur, 2022)
This is a prescribed Grammar and composition textbook for class XI and XII writen in Vaiphei language.
Keywords: Vaiphei; Vaiphei Pau Matdan & Thuphuak (Vaiphei Grammar and Composition) for Class XI & XII); Grammar & Composition; Vaiphei; Vaiphei